Cervical cancer: an unanticipated consequence of high-risk human papillomavirus infection - Walterhouse, Stephen James (Kansas State University, 2018)
Cancer is not a single story, but rather numerous often interwoven tales, each with its own characters and progression. In the case of human papillomavirus (HPV) induced cervical cancer (CaCx), the narrative is about the relationship between virus and host, with the consequences of evolution’s shortsightedness driving the plot. Along with the increased proliferative state characteristic of cancer, cells experience frequent, inaccurate replication and replication stresses (ex. DNA damage and nucleotide starvation). To prevent replication fork stall and collapse generated by these stresses, the cell employs translesion synthesis (TLS). Notably, most of the genes in this pathway are upregulated in CaCx; however, the key protein polymerase eta is not. We have observed that upregulation in this pathway is complicated. It occurs at numerous levels, increasing both mRNA and protein abundance. This research further dissects how TLS upregulation occurs. Data shows that in CaCx-derived cell lines, the stability of some TLS proteins is increased, while the stability of other TLS proteins is unchanged. The increased proliferation, typical of these cell lines, cannot account for the enhanced stability. Despite increased TLS protein stability, these cells fail to adequately activate TLS increasing the risk of DNA damage. Genomic instability is a driving factor in HPV genome integration that prevents viral propagation and leads to cell transformation. It also raises mutagenesis rates, likely creating a selective pressure for tolerating failed TLS. The elevated mutation rate known to be associated with failed TLS could also provide a mechanism for acquired resistance to the drugs commonly used to treat CaCx. Changes in protein abundance are routinely used as biomarkers that can lead to the improved outcomes associated with early cancer detection. Elevated TLS protein could be leveraged to ensure cervical cancers are detected during Stage 1, when the 5-year survival rate is 80-90%, rather than at Stage IV, when the rate dips to around 15%.
Keywords: Human papilloma virus; Evolution; Translesion synthesis; Protein stability; Cervical cancer